Teoria científica das empresas e participações societárias estatais - TEPSES: governanças pública, corporativa e o caso do Brasil - Cioci, Francisco Carlos Loureiro (2013)
After identifying the existence of a theoretical gap, this work has defined its objective as: the establishment of the foundations for an episteme about the phenomenon, through the development of a theory frame able to: a) guide and support the construction and collective development of a Scientific State-Owned Enterprises and Shareholdings Theory – SSOESTh, and b) to identify elements that enable the development of answers to the central applied question: How should governments define the missions, the performance criteria and the mechanisms of governance for SOEs in a changing environment? Taking into consideration these enterprises’ materiality, their strategic relevance to contemporary states their implications to the globalizations and considering administration as an applied science, all of which demand a societal level of analysis and a multiparadigmatic multidisciplinary approach, the theory frame provided answers to several concerns and problems expressed, some over more than half a century, by authoritative scholars in the field as Pritchett, Seidman, Sherwood, Shepherd, Aharoni, Millward, Hinds and Baumol. Forwarding, through phenomenological reduction, a scientific definition of a universal concept of state-owned enterprise and introducing, inter allia, the concepts of essential state capacity in its bracket – ESCb and of patrimonial state-owned enterprise, that allowed the constructions of a public interest scale; the SSOESTh’s rueschemeyerian focused theory frame dimentionalized public and corporate governances, developed lazarsfeldian typologies for each and merged them in an universal typology – G², bridging both hemipheres of the great dichotomy of law and suporting propositions of universal criteria for missions, performance and mechanisms of governance. A plausibility probe of the focused theory frame was conducted with data from SOES directly controlled by the brazilian state, resulting in high levels of plausibility and quality. Externally, the SSOESTh contributes to several broader cientific challenges as: Balleisen's regulation's knownedge paradox, Schneiders trap, Ikedas/Mises doubt, the reopening of the organization adequacy question by the nobel Simon; additionally providing extensions to: the nobel Williamson's typology of governance structures, Riggs' theory of the prysmatic society, Simon's conception of administration as an applied science, Acemoglu and Robinson's institutionalist formulations and the nobel Stiglitz approaches to state intervention. It also enables: a) Each country to substruct its own empirical typology of SOEs, and so, to customize answers to the central applied question and each SOE management, as well as to analyze their adequacy to public policies and criteria for their privatizations; b) Managers, practitioners and case researchers to use the frame to situate and analyze their enterprises; c) Past researches to be reinterpreted at the light of this new referential and d) Everyone to connect their works with this episteme for which the SSOESTh provides the foundations and is a repository, allowing comparative studies. Finally, it is acknowledged that the degree of relevance of the phenomenon, in global terms, is much higher than initially attributed, due to the identification of its condition as an empirical factor of state capacities, considering that several state collapses and débâcles, which resulted in unbearable costs including innumerable human losses, are attributed to the absence of these capacities.